2011
DOI: 10.1148/radiol.10100625
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated Dual-Head Gamma Imaging for Breast Cancer Screening in Women with Mammographically Dense Breasts

Abstract: Addition of gamma imaging to mammography significantly increased detection of node-negative breast cancer in dense breasts by 7.5 per 1000 women screened (95% CI: 3.6, 15.4). To be clinically important, gamma imaging will need to show equivalent performance at decreased radiation doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 47 publications
1
92
1
1
Order By: Relevance
“…without mammography, with a mean kappa of 0.8, and the agreement of observers with expert consensus (kappa 0.83). This interobserver agreement is higher than that reported in validation studies of other breast imaging modalities [10], including PEM [15], and also when compared to a previous BSGI report evaluating BC screening in women with mammographically dense breasts [16]. In this latter study, two observers retrospectively examined images obtained with a dedicated dual-head gamma camera for the presence of abnormal radiopharmaceutical uptake, using a five-point score (10no abnormality, 50 highly suspicious for malignancy).…”
mentioning
confidence: 78%
“…without mammography, with a mean kappa of 0.8, and the agreement of observers with expert consensus (kappa 0.83). This interobserver agreement is higher than that reported in validation studies of other breast imaging modalities [10], including PEM [15], and also when compared to a previous BSGI report evaluating BC screening in women with mammographically dense breasts [16]. In this latter study, two observers retrospectively examined images obtained with a dedicated dual-head gamma camera for the presence of abnormal radiopharmaceutical uptake, using a five-point score (10no abnormality, 50 highly suspicious for malignancy).…”
mentioning
confidence: 78%
“…For comparison, the effective dose equivalent of digital mammography is approximately 0.44 mSv and 1.2 mSv for digital mammography combined with tomosynthesis (19). Technologic improvements in instrumentation design combined with optimized patient preparation to increase radiopharmaceutical uptake have been pursued to reduce the radiation exposure to levels feasible to consider for breast cancer screening programs (20)(21)(22)(23). Continued research into dose reduction methods or consideration of less frequent screening intervals will facilitate broader acceptance of radionuclidebased supplemental screening approaches in clinical practice.…”
Section: See Page 678mentioning
confidence: 99%
“…It is approved as a diagnostic tool after mammography and is not indicated for screening or as an alternative to biopsy. Typical protocols specify an injection of 740-1,100 MBq (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) into the arm contralateral to the suspected abnormality. Imaging begins 5-10 min after injection, with 10 min per view.…”
Section: Single-photon G Imaging Systems For Dedicated Breast Imagingmentioning
confidence: 99%
“…The largest prospective study of BSGI involved 936 women with dense breasts and at least one risk factor (22). They found that the addition of BSGI increased the sensitivity from 27% to 91% and increased the cancer detection rate by 7.5 per 1,000 women screened.…”
Section: Screening Of Women With Dense Breastsmentioning
confidence: 99%